2011
DOI: 10.1002/bmb.20517
|View full text |Cite
|
Sign up to set email alerts
|

The concept lens diagram: A new mechanism for presenting biochemistry content in terms of “big ideas”

Abstract: A strong, recent movement in tertiary education is the development of conceptual, or “big idea” teaching. The emphasis in course design is now on promoting key understandings, core competencies, and an understanding of connections between different fields. In biochemistry teaching, this radical shift from the content‐based tradition is being driven by the “omics” information explosion; we can no longer teach all the information we have available. Biochemistry is a core, enabling discipline for much of modern s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 16 publications
2
26
0
Order By: Relevance
“…There is precedent for including experimental approaches as a cross-cutting concept in course curriculum design. For example, Rowland and colleagues placed experimental approaches at the center of their concept lens diagram to acknowledge that they underlie all knowledge in biochemistry and that developing these skills supports student understanding of the process of science, a key component of Vision and Change (AAAS, 2011; Rowland et al. , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…There is precedent for including experimental approaches as a cross-cutting concept in course curriculum design. For example, Rowland and colleagues placed experimental approaches at the center of their concept lens diagram to acknowledge that they underlie all knowledge in biochemistry and that developing these skills supports student understanding of the process of science, a key component of Vision and Change (AAAS, 2011; Rowland et al. , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that teaching at the concept level challenged the way educators thought about biochemistry, and stimulated the majority of students to think more deeply about biochemistry and make links between biochemistry and material in other courses (Rowland et al., ). Similar results were noted in a biology lab based on concept‐based teaching.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Teaching conceptually focuses on how meaning is produced, and allows students to “integrate factual information within a context, so that concepts, not only facts, become the foundation of understanding” (Hardin & Richardson, , p. 157). Concept‐based approaches are becoming more prevalent as witnessed by their implementation in nursing (Giddens & Morton, ), biology (Halme, Khodor, Mitchell, & Walker, ; Morse & Jutras, ), biochemistry (Rowland, Smith, Gillam, & Wright, ), early childhood education (Birbili, ), social studies (McCoy & Ketterlin‐Geller, ; Milligan & Wood, ), engineering (Custer, Daugherty, & Meyer, ), mathematics (Eisenhart, Borko, Underhill, Brown, Jones, & Agard, , Rittle‐Johnson & Siegler, ), and more recently in business (Burch, Kendall, & Shaw, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, with the development of consensus concept frameworks for physics (8), chemistry (12), biochemistry (14), and more recently microbiology (11), science instructors can more readily define their course and program learning outcomes based on their discipline’s concept-driven curriculum and rationalize the effectiveness of this design in line with the ongoing push for evidence-based teaching (19, 1). …”
Section: Discussionmentioning
confidence: 99%